Is Russia Too Unique to Learn From Abroad? Elite Views on Foreign Borrowing and the West, 1993-2012 - Rivera W. Sharon (Сравнительная политика, 2016)
For more than two centuries, Russia has struggled to defi ne its historical-cultural relationship with the West, as its intellectual and political elites vigorously debated whether their country should emulate Europe or follow a distinct path of development. This article uses original elite survey data to examine these two propositions. The article reaches two conclusions. First, despite Russia’s long tradition of underscoring its uniqueness, close to three-quarters of Russian bureaucrats and Duma deputies in the mid-1990s were nonetheless willing to borrow from foreign experience, particularly from the models of European welfare capitalism. Second, despite the sharp rise in anti-Western sentiments emanating from the Kremlin over the past decade, as well as Vladimir Putin’s ever-growing emphasis on Russia’s distinctiveness, Russian elites are still surprisingly willing to adopt political and economic models from the West.